Grand Service Design Regional Library Pinrang Regency - Aswar Annas; Nursafitra Nursafitra; Eka Fitra Ramadani Salam; Resky Amalia P (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Pinrang Regency Regional Library Service Grand Design. This study aims to measure 9 indicators of regional library service elements in Pinrang Regency. The study used descriptive quantitative methods, with non-probability sampling technique, measurements with a Likert scale involving 194 respondents, the determination of the sample was carried out by purposive sampling. The results showed that in general the 9 service elements in the regional library of Pinrang Regency received a good rating, while the scoring values for each service element were: elements of clarity and ease of requirements for getting digital-based services in good category with a score of 60%, service elements clarity and ease of procedures for obtaining services. digital-based services in the good category with a value of 51%, the service element of availability of information/guidance to get the service in the good category with a value of 53%, the service element of clarity and suitability of service time in the good category with a value of 62%, the service element of the duration/length of service time (opening hours). & closing hours) good category with a value of 52%, service element of speed of completion of document duplicating time in good category with a value of 46%, service element of clarity and reasonableness of the presence / absence of fees in good category with a value of 55%, service element of speed of response to complaints / complaints in good category with a value of 61%, and elements of follow-up services settlement of complaints/complaints in good category with a score of 64%.